2000
DOI: 10.1046/j.1365-2648.2000.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between men and women on the waiting list for coronary revascularization

Abstract: This study aims to examine the situation for patients on the waiting list for possible coronary revascularization in terms of waiting time, treatment and various aspects of well-being in relation to gender. Patients on the waiting list for coronary angiography, percutaneous transluminal coronary angioplasty or coronary artery bypass grafting in September 1990 were approached with a questionnaire dealing with various aspects as described above. Of the 831 patients who participated in the evaluation, 174 (21%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
2
16
0
4
Order By: Relevance
“…It is true that Bengtson et al [19] reported more nervous reactions by men waiting for coronary revascularization, as compared with women, but the women were more frequently treated with diuretics, and reported a higher frequency of various cardiovascular symptoms, including chest pain, dyspnoea and more sleeping disorders. The women in the control group in the present study were significantly less interested in receiving information, but in the intervention group, the women made telephone calls to the nurse significantly more often than the men.…”
Section: Discussionmentioning
confidence: 96%
“…It is true that Bengtson et al [19] reported more nervous reactions by men waiting for coronary revascularization, as compared with women, but the women were more frequently treated with diuretics, and reported a higher frequency of various cardiovascular symptoms, including chest pain, dyspnoea and more sleeping disorders. The women in the control group in the present study were significantly less interested in receiving information, but in the intervention group, the women made telephone calls to the nurse significantly more often than the men.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, in a study investigating differences between men and women on a waiting list for coronary revascularization, although age was similar for men and women, men had a higher prevalence of previous myocardial infarction and a lower prevalence of previous hypertension [26]. Women reported a higher frequency of chest pain at rest and at night, dyspnea when walking, tachycardia, tiredness, headache, dizziness, sweating, difficulty falling asleep, difficulty waking up, repeated awakening and insomnia [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Sleep disturbances predict cardiac events in both sexes without heart disease symptoms at baseline 5 and premature mortality in the general Swedish population, 1,2,5 and in patients with CAD. [6][7][8] This could be the result of nonrestorative sleep function, immune dysfunction, and/or carbohydrate intolerance occurring secondary to sleep loss. 1,2,7,9,10 The prevalence of and information about sleep disturbances among women with CAD have, in previous studies, usually been obtained strictly from a few separate questions.…”
mentioning
confidence: 97%